Intermediate C programming - Lu, Yung-Hsiang (CRC Press, 2015)
Annotation
"A Chapman & Hall book"--Cover. - Print version record
Keywords: C (Computer program language); C (Langage de programmation); COMPUTERS; Programming Languages; C